The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.20944/preprints201905.0170.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Moving Surface Boundary Layer Control Analysis and the Influence of the Magnus Effect on an Aerofoil with a Leading-Edge Rotating Cylinder

Abstract: A number of experimental and numerical studies point out that incorporating a rotating cylinder can superiorly enhance the aerofoil performance, especially for higher velocity ratios. Yet, there have been less or no studies exploring the effects of lower velocity ratio at a higher Reynolds number. In the present study, we investigated the effects of Moving Surface Boundary-layer Control (MSBC) at lower velocity ratios (i.e. cylinder tangential velocity to free stream velocity) and higher Reynolds number on a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…From the Fig. 3 (a), it is observed that the Lift has decreased when cylinder has been added to the leading edge for all velocity ratios contrary to the researches which proved that adding cylinders at the leadingedge improved lift [13]. It is probably due to the asymmetric nature of the airfoil.…”
Section: Lift Vs Angle Of Attack At Different Ratiosmentioning
confidence: 80%
“…From the Fig. 3 (a), it is observed that the Lift has decreased when cylinder has been added to the leading edge for all velocity ratios contrary to the researches which proved that adding cylinders at the leadingedge improved lift [13]. It is probably due to the asymmetric nature of the airfoil.…”
Section: Lift Vs Angle Of Attack At Different Ratiosmentioning
confidence: 80%